Metal-plated laminate containing organic polysiloxane

By using three-dimensionally crosslinkable organopolysiloxane materials in high-frequency applications and cross-linking adjacent silicon atoms using Si-C bonds, the problems of high and poor working performance of dielectric loss ratio in the prior art are solved, and a binding material with low dielectric loss ratio and excellent working performance are achieved.

JP7674591B2Active Publication Date: 2025-05-09WACKER CHEMIE AG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024507012
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-12
Publication Date
2025-05-09
Estimated Expiration
2041-08-12

AI Technical Summary

Technical Problem

The prior art is difficult to provide low dielectric loss ratio binding materials in high frequency applications, and the workingability and bonding properties of these materials are not good.

Method used

Organopolysiloxanes that can be cross-linked under free radical polymerization conditions are used to cross-link adjacent silicon atoms through Si-C bonds, reducing the polarity of Si-O bonds, thereby reducing the dielectric loss factor, and ensuring high workingability and appropriate adhesion properties of the material through specific formulations and treatment methods.

Benefits of technology

The binding material with dielectric loss ratio below 10 GHz is realized, with excellent workingability and adhesive properties, suitable for metal sandwich films in high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007674591000001
    Figure 0007674591000001
  • Figure 0007674591000002
    Figure 0007674591000002
  • Figure 0007674591000003
    Figure 0007674591000003
Patent Text Reader

Abstract

Formula (I): [O 3-a / 2 R a Si-Y(SiR a O 3-a / 2 ) b ] c (R 1 SiO 3 / 2 ) d (R 2 2SiO 2 / 2 ) e (R 3 3SiO 1 / 2 ) f (SiO 4 / 2 ) g A metal-clad laminate comprising the crosslinkable organopolysiloxane compound of (I), 1 , R 2 , R 3 , a, b, c, d, e, f and g have the definitions given in claim 1, Y is a divalent to dodecavalent organic group having 1 to 24 carbon atoms, and all of the Si-C bonded groups Y, R, R 1 , R 2 and R 3 at least 0.1 mole percent of the crosslinkable organopolysiloxane compound must be aliphatically unsaturated groups, and c+d+e+f+g=1.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to metal-clad laminates comprising crosslinkable organopolysiloxane compounds. [Background technology]

[0002] Copper clad electronic laminates consist of layered materials laminated on one or both sides with electrolytic copper foil having a purity of at least 99.5% according to page 2 of DIN 40802. Here, the laminate serves as support and insulation, the copper layer for the manufacture of the conductor tracks. Among electronic laminates, three products have become important. In these products, the laminate consists of hard paper, epoxy hard paper or epoxy resin-glass fabric.

[0003] Although more expensive than hard paper, epoxy resin-glass fabrics are becoming more and more popular for use in telecommunications, especially where higher frequencies are used. The advantages of such electronic laminates are high mechanical strength, better electrical values ​​when exposed to moisture, and low dielectric loss factor at high frequencies.

[0004] The sequence of events in the manufacture of an electronic laminate is as follows: A paper or fabric web of the laminate, for example a fiberglass web, is impregnated with a resin that acts as a binder. Epoxy polyester, phenolic or melamine are commonly used for this purpose. The impregnated web is then dried, which simultaneously causes precondensation of the resin to the desired extent.

[0005] With the advanced development of high frequency technology into the GHz range for wireless communication, there is an increasing demand for materials suitable for its realization. This concerns all material areas such as copper foil, binders, glass fibers, etc. In the case of binders, epoxy resins traditionally used for the production of copper clad laminates or for the production of printed circuit boards can no longer be used for GHz applications due to their excessively high dielectric loss factor. Polytetrafluoroethylene, which has a very low dielectric loss factor and is therefore easily usable for high frequency applications from this point of view, has other drawbacks, in particular poor processability and poor bonding properties, which means that alternatives are desirable. Polyphenylene ethers, hydrocarbon resins, and variants such as bismaleimides, as well as bismaleimide triazine resins, as well as combinations of the organic polymers mentioned, are currently being intensively studied as binders for this application area, since they combine low dielectric loss factors with excellent mechanical and thermal properties and water repellency.

[0006] Organopolysiloxanes have excellent heat resistance, weather stability, and hydrophobicity, are flame retardant, and have a low dielectric loss factor.

[0007] These property profiles make both the polyphenylene ethers, bismaleimide, bismaleimide triazine, and hydrocarbon resins, as well as the organopolysiloxanes, suitable for use as binders for high frequency copper clad laminates and components such as printed circuit boards and antennas.

[0008] It is therefore obvious both to use silicone resins as binders for these high frequency applications and to combine the positive properties of silicones with those of organic polymers mentioned in order to jointly enhance these performances. Corresponding attempts are already documented in the prior art.

[0009] In organopolysiloxanes, adjacent silicon atoms are primarily connected to one another via oxygen atoms, however, other ways in which adjacent silicon atoms can be connected to one another are also known, for example, units bridged by organic groups.

[0010] Organic groups bridging adjacent silicon atoms, for example, always result from a hydrosilylation reaction in which a Si-H group adds to an unsaturated organic group bonded to silicon. Such reactions are primarily known for the curing of formulations containing these two types of functional groups after the formulation is used to permanently fix the resulting application result, see, for example, US Patent Application Publication No. 2018 / 0370189. They can also be used to produce organopolysiloxanes containing organic groups bridging adjacent silicon atoms to generate chemical species that can be further processed. In these cases, block copolymer structures are always formed, maintaining preformed silicone structures and compositions, in which the starting structures are retained as building block segments. A random distribution of organic substituents bridging two silicon atoms is not possible here. In addition, the number of crosslinking units is limited by the number of terminal functional groups. In particular, it should be noted that if this approach is chosen to fix an already reached final state, a volume shrinkage begins as a result of the curing reaction, leading to stresses in the cured matrix and limiting or reducing mechanical performance. To be able to introduce any number of such crosslinking units into the organopolysiloxane structure, for example if they have a specific function for the selected application, this route is therefore not suitable and limits the invention described, for example, in US Patent Application Publication No. 2018 / 0370189.

[0011] U.S. Pat. No. 10,316,148 discloses a compound of the formula (R 1 SiO 3 / 2 ) a (XR 2 2SiO 1 / 2 ) b (O 1 / 2 SiR 2 2YR 2 2SiO 1 / 2 ))c wherein R 1 and R 2 are mutually independent C1~C 20 Alkyl groups, C6-C 20 Aryl group or C7-C 20 The present invention teaches organopolysiloxanes in which X is an aralkyl group, C2-C 12 Alkanediyl group or C2-C bridge containing 2-7 Si units 12 In the case of a linear Si-H functional siloxane group having an alkanediyl group, Y is a linear siloxane group having 2 to 7 siloxane units, and Y is in each case a crosslinked C2-C 12 It is incorporated into the organopolysiloxane of the invention via an alkanediyl group.

[0012] X is C2~C 12 In the case of an alkanediyl group or a Si-H terminated siloxane group consisting of one or two siloxane units in which two siloxane units are connected by a bridged silphenylene group, Y is a siloxane group comprising two siloxane units in which the two siloxane units are connected to each other by a bridged silphenylene group, and the group Y is in any case a bridged C2-C 12 It is incorporated into the organopolysiloxane of the invention via an alkanediyl group.

[0013] X and Y are selected such that they form exclusively linear structures such that block copolymer organopolysiloxanes are essentially present, (R 1 SiO 3 / 2 ) units are (XR 2 2SiO 1 / 2 ) b (O 1 / 2 SiR 2 2YR 2 2SiO 1 / 2 )) cThere are no unsaturated organic groups that can be brought about by free radical reactions. They are completely consumed in the reaction in which the organopolysiloxane of the invention is produced by hydrosilylation, and the Si-H groups are used in excess, resulting in the production of Si-H terminated organopolysiloxanes.

[0014] a is a number from 0.65 to 0.9, b is a number from 0.1 to 0.35, c is a number from 0 to 0.1, and a+b+c=1.

[0015] The inventive organic polysiloxane of the above invention is an organic polysiloxane (R 1 SiO 3 / 2 )d(R 5 R 2 2SiO 1 / 2 ) e wherein R 5 is an olefinically unsaturated C2-C12 alkenyl group, d is a number from 0.65 to 0.9, e is a number from 0.1 to 0.35, and the formula HR 3 2SiO(R 3 2SiO) n SiR 3 2H linear Si-H terminated organopolysiloxane or of the formula HR 3 2Si-C6H4-SiR 3 It is a 2H disilylbenzene, allowing both double hydrosilylation or just single hydrosilylation of the double Si-H terminated siloxane moiety.

[0016] Both the alkanediyl-bridged building blocks and the phenylene-bridged building blocks are exclusively embedded in the linear segments of the polysiloxane structure, and the silicon atom bridged by the alkanediyl or phenylene group is always bonded to exactly one further silicon atom and is not the starting point for branching by bonding to multiple silicon atoms.

[0017] The organopolysiloxanes according to US Patent No. 10,316,148 exhibit high refractive index, high transparency, and excellent processability for use in optical semiconductor devices. Because they are produced by hydrosilylation reactions, they contain platinum as an impurity.

[0018] US 2015 / 0144987 teaches a hydrosilylatable formulation of alkenyl-functional three-dimensional organopolysiloxane, linear alkenyl-functional organopolysiloxane, linear Si-H-terminated organopolysiloxane containing silphenylene groups, optionally linear Si-H-terminated components without additional silphenylene units, and a hydrosilylation catalyst.After curing by hydrosilylation, the above inventive formulation, like the organopolysiloxane from US 10316148, also has adjacent silicon atoms that are both alkanediyl bridged and phenylene bridged.Phenylene bridged silphenylene units are always linear organopolysiloxane segments in which the silicon atom bridged by the phenylene group is always bonded to exactly one additional silicon atom by Si-O-Si bond, and is not the starting point for branching by bonding to multiple silicon atoms. Due to hydrosilylation reactions, these organopolysiloxanes also contain platinum as an impurity.

[0019] The formulation has a high Abbe number, excellent color stability in optical semiconductor devices and is used for the encapsulation thereof.

[0020] US Patent No. 6,072,016 teaches linear organopolysiloxanes that contain silphenylene groups and can be crosslinked by end groups capable of undergoing condensation. They contain no Si-H functionality or aliphatically unsaturated groups.

[0021] U.S. Pat. No. 6,252,100 discloses a method for preparing linear organopolysiloxanes containing structural units in which two R2Si units are interconnected via a difunctional α,ω-alkanediyl group having 2 to 18 carbon atoms.

[0022] No. 6,034,225 discloses, inter alia, the formula O, which optionally includes a branch point. 1 / 2 R2SiO x YRSiO 2 / 2 and optionally furthermore, at least one unit of O, which may be purely linear on the other hand. 1 / 2 R2SiO x YR2SiO 1 / 2 The present application describes linear organopolysiloxanes having aliphatically unsaturated groups containing units. When X=0, either a dialkylsiloxy unit connects two adjacent silicon atoms via an oxygen atom, or / and two dialkylsiloxy units are connected to each other via a spacer Y. Y is a group of the formula -(CR 3 2) n CHR- bifunctional group, where R 3 is an aliphatic saturated hydrocarbon group or H, and n is 0 or an integer from 1 to 7.

[0023] H-Si compounds and organopolysiloxane compounds having active hydrogen in the form of hydrocarbons and hydrocarbon bridges between two Si atoms are described in EP-A-786463, as well as in JP-A-06-107949 and U.S. Pat. No. 4,849,491.

[0024] US Patent Application Publication No. 2010 / 0137544 discloses a compound having the general formula (I): O 3-a / 2 RaSi-Y(SiR a O 3-a / 2 ) b where R, which may be the same or different, is a monovalent SiC-bonded organic group having 1 to 30 carbon atoms and may contain one or more nitrogen and / or oxygen atoms; Y is a divalent to dodecavalent organic group having 1 to 30 carbon atoms and may contain one or more oxygen atoms; a is 0 or 1; and b is an integer from 1 to 11. Summary of the Invention [Problem to be solved by the invention]

[0025] The present invention is directed to the object of providing an organopolysiloxane that can be crosslinked in three dimensions under conditions of free radical polymerization and that has dielectric properties suitable for use as a binder in high frequency applications. The relevant requirements are that the organopolysiloxane, as a pure binder, has a dielectric loss factor at 10 GHz of 0.0040 or less, that any fillers present that reduce the dielectric loss factor are sufficiently wetted, and that the organopolysiloxane allows for the manufacture of adhesive-free prepregs. [Means for solving the problem]

[0026] The present invention relates to a compound of formula (I): [O 3-a / 2 R a Si-Y(SiR a O 3-a / 2 ) b ] c (R 1 SiO 3 / 2 ) d (R 2 2SiO 2 / 2 ) e (R 3 3SiO 1 / 2 ) f (SiO 4 / 2 ) g (I) wherein, in the above formula (I), R may be the same or different and is a hydrogen group or a monovalent SiC-bonded organic hydrocarbon group having 1 to 18 carbon atoms and optionally substituted with a heteroatom, and may be an unsaturated hydrocarbon group; Y is a divalent to dodecavalent organic group having 1 to 24 carbon atoms and optionally substituted with a heteroatom, and the group Y is always bonded to silicon atoms that are mutually connected by the group Y through a Si-C bond; R 1are each independently a hydrogen group or a SiC-bonded unsaturated C1-C18 hydrocarbon group which may be substituted by a heteroatom and which may be bonded to the silicon atom by an oxygen atom, and the group R 1 may assume these meanings independently of one another, so that several radicals R 1 may be a group different from the groups defined above, base R 2 and R 3 are each independently a hydrogen group, or a SiC-bonded C1-C18 hydrocarbon group which may be substituted with a heteroatom and which may be unsaturated, or a C1-C12 hydrocarbon group which contains a heteroatom and which may be bonded with an oxygen atom, and the group R 2 and the above group R 3 may assume each of these meanings independently of one another, so that several groups R 2 or multiple groups R 3 may be a group different from the groups defined above, All SiC-bonded groups Y, R 1 , R 2 , and R 3 At least 0.1 mol %, preferably at least 3 mol %, more preferably at least 5 mol %, in particular at least 7 mol %, based on 100 mol %, must be aliphatic, i.e. olefinically or acetylenically unsaturated groups; a is 0, 1 or 2, and the subscripts a on either side of the group Y may assume each of these meanings independently of one another, so that the different a's may, independently of one another, be different values ​​within the range of values ​​specified, b is a number having a value of 1 to 11, preferably 1; c is a value of 0.1 to 0.99, preferably 0.2 to 0.98, more preferably 0.25 to 0.8, and particularly preferably 0.3 to 0.8; d is a value of 0 to 0.8, preferably 0.1 to 0.7, more preferably 0.1 to 0.6, and particularly preferably 0.1 to 0.5; e is a value of 0 to 0.5, preferably 0 to 0.2; f is a value between 0.01 and 0.6; g is a value between 0 and 0.2; c+d+e+f+g=1. This relates to metal clad laminates.

[0027] The organopolysiloxane of formula (I) acts as a binder and / or adhesion promoter for metal-clad laminates. The organopolysiloxane of formula (I) is crosslinked before the laminate is used. The laminate is preferably a metal-clad laminate. The laminate is preferably used in electronic components, preferably in high frequency applications, most preferably those operating at frequencies above 1 GHz.

[0028] Surprisingly, it has been found that suitable organopolysiloxanes having unsaturated organic functional groups or formulations thereof are particularly well suited for this purpose, which, in addition to regular siloxane units connected by oxygen atoms, further comprise building blocks which are bridged and connected to one another by bridging alkylene, aralkylene or arylene units in which adjacent silicon atoms are linked on either side not by oxygen atoms but by Si-C bonds, with the proviso that polar heteroatom-substituted groups on said organopolysiloxanes are at the same time avoided, i.e. reduced as far as possible by suitable state-of-the-art means, including in particular alkoxy and silanol groups. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Polar groups such as alkoxy groups, particularly short chain alkyl groups and silanol groups, by themselves have a relatively high dielectric loss factor and further contribute to increasing the dielectric loss factor by forming bonding sites for moisture.

[0030] The electronegativity difference between silicon and oxygen based on the Allred-Rochow electronegativity scale is 1.76, which is 1 more than the electronegativity difference between silicon and carbon based on the same table, meaning that the Si-C bond has a lower polarity than the Si-O bond. It is therefore expected that the replacement of Si-O bonds with Si-C bonds will help to reduce the overall polarity of the organopolysiloxane and therefore the dielectric loss factor of the corresponding component. The larger the Si-O bonds that can be replaced by Si-C bonds, the more significant this effect is. Thus, the reduction of polarity in the organopolysiloxane backbone, for example by introducing Si-C bonds instead of Si-O, contributes greatly to the widespread usability of such organopolysiloxanes.

[0031] Since the organic polysiloxanes, which are oils, do not have binder properties, they are not suitable as binders for metal-clad composites. US Patent Application Publication No. 2018 / 0370189 accordingly describes the use of silicone resins as binders with silicone oils used purely to adjust their viscosity, and curing to produce block copolymers. However, the actual binder is silicone resin, not silicone oil. However, the possibilities present for this are not explicitly recognized, so there is no proposal therein for targeted adjustment and optimization of the silicone resins used for the uses described in US Patent Application Publication No. 2018 / 0370189.

[0032] The present invention is an improvement over the prior art described in US 2018 / 0370189 A1 and develops it further, since it is sufficient to allow the SiC-bonded organic groups bridging adjacent silicon atoms to be generated solely by curing any existing Si-H and Si-olefin groups by hydrosilylation at the end of the application process, in order to be able to take advantage of the curing of the siloxane backbone polarity reduction in a targeted manner. The associated volume shrinkage due to the addition reaction described in US 2018 / 0370189 A1 imposes an excessively narrow limit on the property-based use of this option.

[0033] The organopolysiloxane compounds of formula (I) have a dielectric loss factor at 10 GHz of less than or equal to 0.0040.

[0034] Organopolysiloxane compounds of formula (I), in the context of the present invention, include both polymeric and oligomeric organopolysiloxanes.

[0035] In particular, the compound of formula (Ia): [O 3-a / 2 R a Si-Y(SiR a O 3-a / 2 ) b ] c (R 3 3SiO 1 / 2 ) f (Ia) where d, e, and g are each zero. This limiting structure is within the scope and for the purposes of the present invention. The proportion of SiC-bonded bridging organic groups therein is particularly high, and the structure is substantially composed of terminal units (R 3 3SiO 1 / 2 ) f In a preferred embodiment of (Ia), a has a value of 2. R, R 3 All of the above for a, b, and c are also valid for (Ia).

[0036] R, R 1 , R 2, and R 3 Examples of the aryl groups include saturated or unsaturated hydrocarbon groups which may contain aromatic or aliphatic double bonds, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, and tert-pentyl groups, hexyl groups such as n-hexyl, heptyl groups such as n-heptyl, octyl groups such as n-octyl, and isooctyl groups such as 2,2,4-trimethylpentyl and 2-ethylhexyl, nonyl groups such as n-nonyl, decyl groups such as n-decyl, dodecyl groups such as n-dodecyl, tetradecyl groups such as n-tetradecyl, n-hexadecyl, and the like. cycloalkyl groups such as cyclopentyl, cyclohexyl, and 4-ethylcyclohexyl, cycloheptyl, norbornyl, and methylcyclohexyl groups; aryl groups such as phenyl, biphenyl, naphthyl, anthryl, and phenanthryl groups; alkaryl groups such as o-, m-, p-tolyl, xylyl, and ethylphenyl groups; aralkyl groups such as benzyl groups; alkenyl groups such as 7-octenyl, 5-hexenyl, 3-butenyl, allyl, and vinyl groups; and also α- and β-phenylethyl groups.

[0037] Group R, R 1 , R 2 , and R 3 Preferred heteroatoms which may be present in are oxygen atoms. In addition, nitrogen atoms, phosphorus atoms, sulfur atoms, and halogen atoms such as chlorine and fluorine atoms are also possible.

[0038] Preferred heteroatom-containing organic groups R, R 1 , R 2 , and R 3Examples of the acrylic or methacrylic acid groups are those containing the respective acryloyloxy or methacryloyloxy groups of acrylic acid or methacrylic acid esters of unbranched or branched alcohols having 1 to 15 carbon atoms. Among such groups, preferred are those derived from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, t-butyl acrylate, t-butyl methacrylate, 2-ethylhexyl acrylate, and norbornyl acrylate. Particularly preferred are methyl acrylate, methyl methacrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, and norbornyl acrylate.

[0039] These groups are preferably not directly bonded to the silicon atom, but are bonded by a hydrocarbon spacer which may contain 1 to 12 carbon atoms, preferably 1 or 3 carbon atoms, and do not contain any further heteroatoms other than those present in the acryloyloxy or methacryloyloxy group.

[0040] Further preferred heteroatom-containing groups R, R 1 , R 2 , and R 3 is represented by formula (II):

[0041] [ka] It is of the following.

[0042] Preferably, the hydrocarbon groups R, R 1 , R 2 , and R 3 is selected from methyl, phenyl, vinyl, acryloyloxy, and methacryloyloxy groups and acrylic or methacrylic acid esters of unbranched or branched alcohols having 1 to 15 carbon atoms.

[0043] In formula (II), R 4 , R 5 , R 6 , R 7 , R 8 , and R 9 are each independently a hydrogen group, a hydrocarbon group or a heteroatom-substituted hydrocarbon group, and the group R 4 , R 5 , R 6 , R 7 or R 8 is a hydrocarbon group bonded to a silicon atom by a Si-C or Si-O-C bond, whereby the hydrocarbon group to which the group of formula (II) is bonded to a silicon atom is preferably a C3 hydrocarbon group containing no heteroatoms. 4 , R 5 , R 6 , R 7 or R 8 may be a chemical bond, such that the group of formula (II) is bonded directly to the silicon atom by a Si-C bond via said group which is a chemical bond.

[0044] base R 4 , R 5 , R 6 , R 7 , R 8 or R 9Examples of are saturated hydrocarbon groups such as hydrogen, methyl, ethyl, n-propyl, and isopropyl groups; aromatic groups such as primary, secondary, and tertiary butyl groups, hydroxyethyl, phenylethyl, phenyl, benzyl, methylphenyl, dimethylphenyl, ethylphenyl groups; heteroatom-containing groups such as hydroxymethyl, carboxyethyl, methoxycarbonylethyl, and cyanoethyl groups; and acrylic and methacrylic acid groups such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, t-butyl acrylate, t-butyl methacrylate, 2-ethylhexyl acrylate, and norbornyl acrylate; and olefinically or acetylenically unsaturated hydrocarbon groups.

[0045] If necessary, the adjacent group R 4 and R 6 and the adjacent group R 5 and R 7 can be connected to each other to produce the same cyclic saturated or unsaturated group, thus resulting in a fused polycyclic structure.

[0046] Examples of phenol groups of formula (II) are phenol, ortho-, meta- or para-cresol, 2,6-, 2,5-, 2,4- or 3,5-dimethylphenol, 2-methyl-6-phenylphenol, 2,6-diphenylphenol, 2,6-diethylphenol, 2-methyl-6-ethylphenol, 2,3,5-, 2,3,6- or 2,4,6-trimethylphenol, 3-methyl-6-tert-butylphenol, thymol and 2-methyl-6-allylphenol, which may be substituted at the oxygen atom.

[0047] Preferred examples of fluorine-containing groups are trifluoropropyl, nonafluorohexyl, and heptadecafluorooctyl groups.

[0048] Y is preferably a connecting organic unit having 1 to 24 carbon atoms between 2 to 12 siloxanyl units. Y is preferably divalent, trivalent or tetravalent, in particular divalent.

[0049] Preferred bridging aromatic groups Y are represented by formulae (IIIa), (IIIb), and (IIIc):

[0050] [ka] The

[0051] In the formula, the group R 10 , R 11 , R 12 , and R 13 is a hydrogen group or an optionally substituted hydrocarbon group or R 14 is a hydrocarbon radical of the formula OR 14 In formula (IIIa), the adjacent group, e.g. R 10 and R 12 or R 11 and R 13 may be linked together to form a cyclic group, thus giving rise to a fused ring system.

[0052] Typical examples of such bridging aromatic groups are p-, m- or o-phenylene groups, 2-methyl-1,4-phenylene groups, and 2-methoxy-1,4-phenylene groups, with the p-phenylene group being particularly preferred.

[0053] If desired, a number of such groups may be linked together, for example, such that two or more units of formula (IIIa) are linked together, the oligomeric bridge structural element being present through bonds between corresponding carbon atoms and silicon atoms of the terminal aromatic rings. The aromatic units may be linked together directly or through a linking group such as an alkanediyl unit, e.g., a methylene group, a 1,2-ethanediyl group, a 1,1-ethanediyl group, a 2,2-dimethylpropyl group or a sulfone group.

[0054] Further examples of aromatic bridging units are those in which the optionally disubstituted phenol ring is bridged by alkanediyl or other units.Typical representatives are the 2,2-bis(4-hydroxyphenyl)propane group (substituted bisphenol A group), the 2,2-bis(4-hydroxyphenyl)methane group (substituted bisphenol F group), and the bis(4-hydroxyphenyl)sulfone group (bisphenol S group) which are substituted at the phenolic oxygen atom, and the phenolic oxygen atom is usually replaced by a group of the -(C3H6)- type, which is bonded to the silicon atom by SiC, thereby forming a bridge.

[0055] Preferred groups Y that are not bridged by aromatic units are alkanediyl, alkenediyl and alkynediyl groups, which may optionally contain heteroatoms and aromatic groups as substituents, but which do not assume or contribute to the bridging function in these groups.

[0056] Typical examples are methylene, methine, tetravalent carbon, 1,1-ethanediyl and 1,2-ethanediyl, 1,4-butanediyl and 1,3-butanediyl, 1,5-pentanediyl, 1,6-hexanediyl, 1,7-heptanediyl, 1,8-octanediyl, 1,9-nonanediyl, 1,10-decanediyl, 1,11-undecanediyl and 1,12-dodecanediyl, 1,2-diphenylethanediyl, 1,2-phenylethanediol and 1,2-cyclohexylethanediyl. When the linear bridging unit has more than one carbon atom and the substitution pattern permits this, each of these groups may also function as a bridge through other connectivity, i.e. other than that resulting from the use of different chain atoms, α,ω connectivity, i.e. through the first and last atoms, respectively, of the linear unit. Representative examples further include not only the linear representatives of the mentioned bridged hydrocarbons, but also their isomers, which in turn can function as bridges through bonds between different carbon atoms and silicon atoms of the hydrocarbon structure.

[0057] Examples of particularly preferred groups from the group of non-aromatic non-heteroatom-containing hydrocarbon groups are -CH2CH2-, -CH(CH3)-, -CH=CH-, -C(=CH2)-, and -C≡C-.

[0058] Examples of typical fluorine-substituted bridging groups Y are -C(CF3)2-, -C(H)FC(H)F-, and -C(F2)-C(F2)- groups.

[0059] Typical examples of heteroatom-containing bridging groups are, for example, ethyleneoxypropylene and ethyleneoxybutylene groups. Further typical examples are, bilaterally, -(CH2) n - or -CH2-CH(R 15 )-C(=O)O- terminal group, where n is typically 3 to 8, and R 15 is a hydrogen atom or a methyl group and a glycol group or a phenylene ether group bonded to the silicon atom by this terminal group.

[0060] The entire list is by way of example only and should not be construed as limiting.

[0061] The organopolysiloxane compounds of formula (I) may vary in viscosity over a wide range depending on the average number per molecule of the structural units from which they are formed, or the organopolysiloxane compounds of formula (I) may be solids.

[0062] The liquid organopolysiloxane compound of formula (I) in the uncrosslinked state preferably has a viscosity at 25°C of 20 to 8 million mPa·s, more preferably 20 to 5 million mPa·s, especially 20 to 3 million mPa·s.

[0063] The solid organopolysiloxane compounds of formula (I) in the non-crosslinked state preferably have a glass transition temperature of 25° C. to 250° C., more preferably 30° C. to 230° C., in particular 30° C. to 200° C. Organopolysiloxanes with bridged phenylene units and an overall aromaticity ratio of at least 20 mol % relative to the SiC-bonded substituents as 100 mol % have been found to be particularly suitable. Phenylene units are understood to mean substituted or unsubstituted phenylene units of monomers as well as oligomers, as described in the examples which illustrate the nature of this type of bridged substituent.

[0064] The organopolysiloxane compounds of formula (I) may be prepared by any desired method. A preferred method for preparing these compounds is by reacting the organopolysiloxane compounds of general formula (IV): X3-aRaSi-Y(SiR a X 3-a ) b (IV) and hydrolysis of a compound of formula (V): R 16 h Six 4-h (V), and wherein X is a hydrolyzable group; H is an integer from 0 to 3, R 16 When h=1, the group R 1 and when h=2, R 2 and if h=3, then R 3 and and R, Y, a, and b are as already defined above.

[0065] Compounds (IV) can be obtained by prior art methods, the type of reaction used being highly dependent on the composition of the respective compound (IV). Compounds (IV) are usually obtained, for example, by hydrosilylation from olefinically unsaturated organic precursors, such as acetylene and diallyl or divinyl compounds, and Si-H functional silicone building blocks.

[0066] Grignard reaction from halogenated organic precursors and then reaction with halogenated or alkoxylated organosilanes are also considered here.If necessary, it is also possible to use metal halide exchange reaction of halogenated organic precursors with alkyl compounds of alkali metals such as butyl lithium, followed by coupling reaction with known silicone building blocks.Such methods are known to those skilled in the art and can be easily utilized and understood from available literature.Since these methods are not the subject of the present invention, everything provided in this respect is a reference to the prior art that is documented and searchable.

[0067] The relative ratio in which the compound of formula (IV) is co-condensed with the compound of formula (V) is determined by the values ​​of the subscripts c, d, e, f, and g in formula (I).

[0068] Preferably, X is a halogen, acid or alkoxy group, more preferably chlorine, acetate, formate, a methoxy group or an ethoxy group.

[0069] If desired, the organosiloxanes obtained in this manner may be modified by further reactions, for example by use of known prior art methods, to further alter and modify the equilibrium so that it is possible to produce practically any desired branched siloxane oligomers and polymers and silicone resins, all of which are understood in the context of the present invention as belonging to the term organopolysiloxane.

[0070] Preferably, the cohydrolysis is carried out such that a mixture of compounds (IV) and (V) is metered into water or dilute acid while cooling. In the case of gaseous acids such as HCl, metered addition into concentrated aqueous HCl is also useful for recovering the acid released as gas. Since the hydrolysis is variably exothermic depending on the nature of the group X, cooling is necessary both for the safe conduct of the reaction and, if necessary, to avoid side reactions in the corresponding steps of the synthesis. However, the use of high temperatures may be advantageous and necessary to drive the reaction to completion.

[0071] The reaction times for chlorosilanes are usually very short, so that the time required to carry out the process in batch operation depends mainly on the cooling capacity. Alternatively, the cohydrolysis of (IV) and (V) can also be carried out continuously, for which both loop reactors and also column and tubular reactors are suitable.

[0072] To reduce residual acid, extensive washing with water, clean phase separation, and purification of the hydrolysis product under low pressure are advantageous.

[0073] The process can be carried out at standard pressure, however, higher or lower pressures are also practical depending on the purpose.

[0074] Formula (R 3 3SiO 1 / 2 ) f By using groups of the formula (R), it is possible to both control the molecular weight and reduce the alkoxy and silanol groups during the synthesis. If this is done in the hydrolysis process, the latter are generated during the synthesis, which is the preferred embodiment. Chlorosilane precursors are used to prepare alkoxy groups of the formula (R 3 3SiO 1 / 2 ) f In the course of synthesis, when preparing the group, symmetrical disiloxanes are also formed from this, which can be repeatedly cleaved under acidic hydrolysis conditions and thus remain available as end groups for reaction with the silanol groups formed in the organopolysiloxane after hydrolysis of the chlorosilane starting material. This allows the reduction of silanol groups. Alkoxy groups, especially those with small alkyl groups, also form silanol groups under acidic hydrolysis conditions, the short-chain alcohols are cleaved and the alkoxy groups are reduced by the use of terminal building blocks. In particular, when any remaining disiloxanes are replaced exclusively or exclusively by short-chain alkyl groups, especially methyl groups, they can usually be distilled off at the end of the synthesis, so that they can also be used in excess here.

[0075] It is also possible to selectively bring about a reduction in the silanol groups by adding chlorosilanes or disiloxanes which generate these end groups separately in the final step of the synthesis and by acidic hydrolysis conditions. Here, it is always advantageous to use an excess of terminal chlorosilanes and to remove the resulting disiloxanes by distillation. Vinyldimethylchlorosilane, dimethylchlorosilane or trimethylchlorosilane can be used particularly advantageously for this purpose, since the resulting disiloxanes can be particularly easily separated by distillation. Alternatively, it is also possible to use the disiloxanes immediately and to select hydrolysis conditions which require the addition of sufficient amounts of catalytically active acid, preferably hydrochloric acid. The amount of hydrochloric acid used in this case is usually 50 to 1000 ppm relative to the amount of siloxane in the reaction mixture.

[0076] A residual silanol content of less than 1% by weight is achieved. The complete elimination of the silanol content to the technically possible minimum is not the subject of this invention, and therefore the process is not further optimized.

[0077] Preferably, the metal clad laminate comprises a formulation comprising the organopolysiloxane compound of formula (I) and a further component.

[0078] The organopolysiloxane compounds of formula (I) are chemically cured, i.e., cured by chemical reaction to produce a crosslinked, insoluble network. Curing occurs via the olefinically unsaturated groups described herein above. Usually, free radical polymerization reactions are used for curing, or - in the case where silicon-bonded hydrogen is also present as a group in addition to the olefinically or ethylenically unsaturated functional groups - they are cured by hydrosilylation.

[0079] All organopolysiloxane compounds of formula (I) have aliphatically unsaturated functional groups that can be chemically crosslinked.Possible chemical crosslinking reactions here include known reactions in the prior art, in particular free radical crosslinking, which can be initiated both by suitable radiation sources, such as UV light, unstable chemical compounds that break down into further radicals, as well as addition crosslinking, for example hydrosilylation of olefinically unsaturated groups with Si-H functional groups in the presence of suitable hydrosilylation catalysts, which are further constituents of the formulation.

[0080] In order to achieve sufficient curing, a sufficient amount of functional groups must be present. In order to achieve sufficient curing, an average of at least 1.0 functional groups must be present per molecule of the organopolysiloxane compound of formula (I), preferably an average of at least 1.1, in particular an average of at least 1.2 functional groups must be present per molecule of the organopolysiloxane compound of formula (I). The functional groups here may be different, so that, for example, one part of the functional groups is a Si-H group and another part of the functional groups is an olefinically unsaturated group that is curable or hydrosilylatable by free radicals. Further combinations of complementary functional groups are also conceivable, where complementation means that the selected combination of functional groups can react with each other. If only one type of functional group is present, for example a single olefinically or acetylenically unsaturated functional group that is curable by free radicals, a corresponding number of these functional groups must be present. For the purpose of copolymerization to produce a homogeneous matrix, it should be ensured that the selected olefin and acetylenic groups have sufficient copolymerizability. Combination olefin groups which cannot copolymerize with each other are also possible, provided that the resulting matrix of two, or optionally more, individual polymers remains compatible with each other and does not produce separate phases which separate into mutually distinguishable domains.

[0081] Thus, as a further component of the formulation, a suitable initiator may be present to initiate the free radical polymerization. Examples of suitable initiators include, inter alia, di-tert-butyl peroxide, dilauryl peroxide, dibenzoyl peroxide, dicumyl peroxide, cumyl peroxy neodecanoate, tert-butyl peroxy neodecanoate, tert-amyl peroxy pivalate, tert-butyl peroxy pivalate, tert-butyl peroxy isobutyrate, tert-butyl peroxy 3,5,5-trimethylhexanoate, tert-butyl cumyl peroxide, tert-butyl peroxy 1,2,3,4,5-trimethylhexanoate ... acetate, tert-butyl peroxybenzoate, 1,1-di-tert-butylperoxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl)peroxydicarbonate, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, dibenzyl peroxydicarbonate, diisopropylbenzene dihydroperoxide, [1,3-phenylenebis(1-methylethylidene)]bis[tert-butyl]peroxy Examples from the field of organic peroxides include peroxyethyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, diacetyl peroxydicarbonate, acetyl acetone peroxide, acetyl cyclohexanesulfonyl peroxide, tert-amyl hydroperoxide, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy isopropyl carbonate, tert-amyl peroxy neodecanoate, tert-amyl peroxy-3,5,5-trimethylhexanoate, tert-butyl monoperoxymaleate, etc., this list being merely illustrative and not limiting. If necessary, it is also possible to use mixtures of different initiators for free radical reactions. The suitability of an initiator or a mixture of initiators for free radical reactions depends on its decomposition reaction rate and the requirements that must be met. Due consideration of these boundary conditions allows the skilled person to select the appropriate initiator.

[0082] For organopolysiloxane compounds of formula (I) containing silicon-bonded hydrogen as well as olefinic and acetylenically unsaturated groups, there is the option of curing via a hydrosilylation reaction. A suitable catalyst for promoting the hydrosilylation reaction may be present as a further component of the formulation.

[0083] Examples of such catalysts are compounds or complexes of the group of precious metals comprising platinum, ruthenium, iridium, rhodium and palladium, preferably metal catalysts from the group of platinum metals or compounds and complexes from the group of platinum group metals. Examples of such catalysts are platinum, metal and particulate platinum, which may be supported on a support such as silicon dioxide, aluminum oxide or activated carbon, platinum halides such as PtCl4, HPtCl6·6H2O, Na2PtCl4·4H2O, platinum olefin complexes, platinum alcohol complexes, platinum alkoxide complexes, platinum ether complexes, platinum aldehyde complexes, platinum ketone complexes including the reaction product of HPtCl4·6H2O with cyclohexanone, platinum 1,3-divinyl-1,1,3,3-tetramethyldisiloxane complexes with or without detectable content of inorganically bound halogen. Gold vinyl siloxane complexes, bis(γ-picoline) platinum chloride, trimethylenedipyridine platinum chloride, dicyclopentadiene platinum dichloride, dimethylsulfoxyethenyl platinum (II) dichloride, cyclooctadiene platinum dichloride, norbornadiene platinum dichloride, γ-picoline platinum dichloride, cyclopentadiene platinum dichloride, and also reaction products of platinum tetrachloride with olefins and primary or secondary amines or primary and secondary amines, such as reaction products of platinum tetrachloride dissolved in 1-octene with sec-butylamine or ammonium platinum complex. In a further embodiment, a complex of iridium with cyclooctadiene is used, for example μ-dichlorobis(cyclooctadiene)diiridium (I).

[0084] This list is illustrative only and not limiting. Hydrosilylation catalyst development is, of course, an active area of ​​research constantly yielding new active species that may be used herein.

[0085] The hydrosilylation catalyst is preferably selected from platinum compounds or complexes, preferably platinum chloride and platinum complexes, especially platinum olefin complexes, more preferably platinum divinyltetramethyldisiloxane complexes.

[0086] In the curing process, the hydrosilylation catalyst is used in an amount of 2 to 250 ppm by weight, preferably in an amount of 3 to 150 ppm by weight, in particular in an amount of 3 to 50 ppm by weight.

[0087] The organopolysiloxane compounds of formula (I) are particularly well suited for use as binders for producing metal clad electronic laminates, such as those used to produce electronic devices, especially printed circuit boards in high frequency applications.

[0088] These metal clad electronic laminates may, but do not necessarily, include a reinforcing material, which may or may not include a reinforcing fabric, such as a textile fabric or nonwoven fabric, for example. When a reinforcing material is present, it is preferably arranged in layers, where the reinforcing layers may consist of a variety of different fibers.

[0089] Such a reinforcing layer helps control shrinkage and provides improved mechanical strength.

[0090] If a reinforcing layer is included, the fibers forming this layer may be selected from a variety of options. A non-limiting list of examples of such fibers includes glass fibers such as E-glass, S-glass, and D-glass, silica fibers, polyetherimide fibers, polysulfone fibers, polyetherketone fibers, polyester fibers, polycarbonate fibers, aromatic polyamide fibers, or liquid crystal fibers. The fibers may have a diameter of 10 nm to 10 μm. The reinforcement has a thickness of 200 μm or less, preferably 150 μm or less.

[0091] A preferred form of use is the use of organopolysiloxane compounds of formula (I) as binders for the further production of printed circuit boards or as co-binders together with organic binders for the production of metal clad laminates from glass fiber composites. The preferred metal is copper.

[0092] The organopolysiloxane compound of formula (I) may be used as a sole binder. A further component of the formulation, an organic binder, may be present. The organic binders used are, for example, organic monomers, oligomers and polymers.

[0093] Organic monomers, oligomers and polymers commonly used for this purpose include polyphenylene ethers, bismaleimides, bismaleimide triazine copolymers, hydrocarbon resins, both aliphatic such as polybutadiene and aromatic such as polystyrene, as well as hybrid systems having both aliphatic and aromatic properties, e.g. styrene-polyolefin copolymers, there is in principle no restriction on the morphology of said copolymers, epoxy resins, cyanate ester resins and others as appropriate, it being understood that these selections are illustrative and non-limiting.

[0094] Preferred organic monomers, oligomers and polymers are oligomeric and polymeric polyphenylene ethers, monomeric, oligomeric and polymeric bismaleimides, oligomeric and polymeric hydrocarbon resins, and bismaleimide-triazine copolymers. If desired, the above organic monomers, oligomers and polymers may be mixed with each other.

[0095] If organic components are additionally used, the proportion of organic monomers, oligomers and polymers in the formulation comprising the organopolysiloxane compound of formula (I) is from 10% to 90%, preferably from 20% to 90%, in particular from 30% to 80%, based on the mixture of organopolysiloxane compounds of formula (I), the organic monomers, oligomers and polymers being taken as 100%.

[0096] In addition, both the organopolysiloxane compounds of formula (I) and their mixtures with organic monomers, oligomers or polymers may be dissolved, if desired as reactive diluents, in further organic monomers having olefinic or acetylenically unsaturated groups, such as styrene, α-methylstyrene, paramethylstyrene and vinylstyrene, chlorostyrene, and bromostyrene.

[0097] Said formulations may comprise as further constituents customary non-reactive solvents for dissolving the organopolysiloxane compounds of formula (I) and, if necessary, their mixtures with organic monomers, oligomers or polymers, for example aliphatic or aromatic solvents such as aliphatic mixtures having a defined boiling range, toluene, xylene, ethylbenzene or mixtures of said aromatic compounds, ketones such as acetone, methyl ethyl ketone, cyclohexanone, carboxylic acid esters such as ethyl acetate, methyl acetate, ethyl formate, methyl formate, methyl propionate, ethyl propionate, and in particular good solubility of mixtures of organopolysiloxane compounds of formula (I) with organic monomers, oligomers and polymers is most likely to be achieved in aromatic solvents such as toluene, xylene, ethylbenzene and mixtures thereof.

[0098] When the organopolysiloxane compound of formula (I) is used in combination with organic oligomers or polymers or their mixtures, it is essential to use an organopolysiloxane compound of formula (I) that is compatible with selected organic components and does not cause phase separation.In such cases, the organopolysiloxane compound of formula (I) that is more phenyl-rich should be used in general, since phenyl groups improve compatibility with organic components.In particular, for organic polymers with larger aromatic components, such as polyphenylene ethers or aromatic hydrocarbon resins, the organopolysiloxane compound of formula (I) with larger aromatic components should be used, and both the bridging aromatic groups and aromatic substituents that are terminally linked to silyl units contribute to adjusting compatibility.

[0099] The exact amount of aromatic groups required to adjust the compatibility of the organopolysiloxane compound of formula (I) with a particular selection of organic binder must be determined depending on the selection of organic binder.

[0100] It is also possible to mix multiple organic polymers selected from different polymer classes as necessary and use them in the binder formulation. It is also possible to combine multiple organopolysiloxane compounds of formula (I) with each other in the binder formulation. In other words, according to the present invention, only a single organopolysiloxane compound of formula (I) is used as a binder, or multiple organopolysiloxane compounds of formula (I) are combined with each other in the binder formulation. Similarly, according to the present invention, only one organopolysiloxane compound of formula (I) is combined with one or more organic polymers in the binder formulation. Furthermore, according to the present invention, multiple organopolysiloxane compounds of formula (I) are combined with one or more organic polymers in the binder formulation.

[0101] The compatibility of one or more organopolysiloxane compounds of formula (I) with one or more organic oligomers or polymers is easily established by mixing a mixture of organic binder and organopolysiloxane compounds of formula (I) in a solvent in which all selected components are advantageously soluble, then removing the solvent by conventional techniques, such as distillation or spray drying, and evaluating the resulting residue visually or by microscopy or, if necessary, by electron microscopy. A compatible mixture can be recognized by the absence of silicone domains that are separate from the organic components and recognizable as a different phase.

[0102] As further components, the formulation may comprise further formulation components such as additives, if necessary, silanes, for example defoamers and degassers, wetting and dispersing agents, leveling agents, compatibilizers, adhesion promoters, curing initiators, catalysts, stabilizers, fillers including pigments, dyes, inhibitors, flame retardants, and crosslinking coagents. In addition to testing for compatibility in the sense of appropriate miscibility behavior, compatibility tests regarding reactivity may also be necessary, both to prevent premature gelation and to ensure that sufficiently rapid polymerization / copolymerization of all components with each other is achieved during curing, as well as tests for sufficient wetting and other properties if necessary. This must be observed and taken into account in the preparation of the formulation if necessary.

[0103] Examples of fillers that can be used are ceramic fillers such as silica (e.g. precipitated silica or fumed silica, which may be hydrophilic or hydrophobic, preferably hydrophilic, and may additionally be provided functionally and optionally reactively with organic groups on their surface), quartz (which may be surface treated or surface functionalized so as to have reactive functional groups on its surface), aluminum oxide, aluminum hydroxide, calcium carbonate, talc, mica, clay, kaolin, magnesium sulfate, carbon black, titanium dioxide, zinc oxide, antimony trioxide, barium titanate, strontium titanate, corundum, wollastonite, zirconium tungstate, ceramic hollow spheres, aluminum nitride, silicon carbide, beryllium oxide, magnesium oxide, magnesium hydroxide, solid glass spheres, hollow glass spheres, and boron nitride. As further fillers it is possible to use various materials, for example core-shell particles made of silica surface-coated silicone resin spheres or polymer-coated elastomer particles, said elastomer particles may be silicone elastomers, a typical example of the surface coating of such elastomer particles is a polymethyl methacrylate shell. Preferably, the ceramic filler has a D of 0.1 μm to 10 μm. 90The particle size is expressed as a value. Preferably, the filler is present in an amount of 0.1 to 60% by weight, preferably 0.5 to 60% by weight, in particular 1 to 60% by weight, based on 100% of the total binder formulation consisting of the binder, the respective monomers, additives and fillers. This means that any non-reactive solvent used is not included.

[0104] In the case of fillers, particular mention should be made of those which are thermally conductive: aluminium nitride, boron nitride, silicon carbide, diamond, graphite, beryllium oxide, zinc oxide, zirconium silicate, magnesium oxide, silicon oxide and aluminium oxide.

[0105] The binder formulation may in principle contain a flame retardant, usually in an amount of 5-25% by weight. However, this is a special feature of the organopolysiloxane compound of formula (I) which reduces the need for a flame retardant, since the organopolysiloxane compound of formula (I) itself already exhibits flame retardant properties. Polysilsesquioxanes and siloxanes are known to exhibit flame retardant properties and their use as flame retardants is prior art. Thus, a particular advantage of the present invention is that it is now possible to combine the functionality of the binder with a flame retardant functionality. Thus, depending on the amount of organopolysiloxane compound of formula (I) used, it is possible to reduce the amount of flame retardant. If the amount used is at least 20% by weight, based on the total mixture of all binders and reactive organic monomers used, the amount of flame retardant still present is preferably only 0-10% by weight, more preferably 0-8% by weight, in particular 0-5% by weight; in other words, the use of organopolysiloxane compounds of formula (I) makes it possible to dispense with the use of flame retardants, depending on the organopolysiloxane selected and the amount used.

[0106] Typical examples of flame retardants are hydrates of the metals Al, Mg, Ca, Fe, Zn, Ba, Cu or Ni, and borates of Ba and Zn. The flame retardants may be surface-treated, so that they have reactive groups on their surface. The flame retardants may be halogenated organic flame retardants such as hexachloroendomethylenetetrahydrophthalic acid, tetrabromophthalic acid or dibromoneopentyl glycol. Examples of other flame retardants are phosphorus-containing components such as melamine cyanurate and phosphinates, diphosphinates, phosphazenes, vinylphosphazenes, phosphonates, phosphaphenanthrene oxides, and fine-grained melamine polyphosphate.

[0107] Further examples of bromine-containing flame retardants are bis(pentabromophenyl)ethane, ethylene bis(tetrabromo)phthalimide, tetradecabromodiphenoxybenzene, decabromodiphenyl oxide or brominated polysilsesquioxanes. Some flame retardants synergistically enhance each other's effect. This is the case, for example, of the combination of a halogenated flame retardant with antimony trioxide.

[0108] The formulation may contain as further components antioxidants, stabilizers against deterioration due to weathering, lubricants, plasticizers, colorants, phosphorescent agents or other agents for marking and traceability purposes, and antistatic agents.

[0109] The crosslinking coagents used are in particular polyunsaturated monomers and oligomers that are curable or hydrosilylatable by free radicals, as illustrated in the following non-limiting examples: Examples include doubly olefinically unsaturated components, such as symmetrical olefinically unsaturated disubstituted disiloxanes, such as 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, 1,1,3,3-tetramethyl-1,3-dipropylmethacryloyldisiloxane, doubly olefinically unsaturated disubstituted organic monomers, such as diallyl-, divinyl-, diacryloyl- or dimethacryloyl-substituted, or oligomers, such as conjugated and non-conjugated dienes, such as 1,9-decadiene and 1,3-butadiene. These also include unsaturated monomers or oligomers having three olefinically unsaturated bonds, such as 1,2,4-trivinylcyclohexane, triallyl cyanurate or triallyl isocyanurate, and tri(meth)acrylates, for example trimethylolpropane trimethacrylate.

[0110] These also include unsaturated substituted monomers and oligomers having four unsaturated bonds, such as 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, 2,4,6,8-tetraphenyl-2,4,6,8-tetravinylcyclotetrasiloxane, 2,2-bis[[(2-methyl-1-oxoallyl)oxy]methyl]-1,3-propanediylbismethacrylate (pentaerythritol tetramethacrylate), tetraallyl orthosilicate, tetraallyl-cis,cis,cis,cis-1,2,3,4-cyclopentanetetracarboxylate, tetraallylsilane, and glyoxal bis(diallyl acetal).

[0111] In addition to free radical curing, curing by hydrosilylation is also conceivable, so that polyvalent Si-H functional components can also function as crosslinkers, e.g. 1,1,3,3-tetramethyl-1,3-disiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 1,4-bis(dimethylsilyl)benzene or organooligosiloxanes and organopolysiloxanes with polyvalent Si-H functionalities in the chain and / or at the end.

[0112] Useful catalysts / initiators for the free radical curing of the organopolysiloxane compound of formula (I) and the binder formulation of organic monomers, oligomers, and polymers are the same as those already described herein.In addition, other free radical starters suitable for initiating the free radical curing of both the organopolysiloxane compound of formula (I) and the binder formulation described are azo components such as α,α'azobis(isobutyronitrile), redox initiators, for example, combinations of peroxides such as hydrogen peroxide and iron salts, or azides such as acetyl azide.

[0113] The organopolysiloxane compounds of formula (I) and formulations comprising them may be used according to the invention for use both as solvent-free and solvent-containing formulations. They are generally used in the form of solvent-containing formulations in order to promote homogeneous interdispersion of all the components of the formulation and wetting and impregnation of any reinforcing layer used. The reinforcing layer is generally used. Preferably, this is a glass fiber fabric. The impregnation of the reinforcing layer can be carried out by impregnation application of the formulation, for which there are various available technical solutions, including, if necessary, a continuous process for the manufacture of the metal-clad laminate of the invention, and its selection. Non-limiting examples of application techniques are dipping, spraying, flooding, knife coating, etc. of the web of reinforcement by a roller system, if necessary in a continuous process. It is an advantage of the present invention that all available techniques may be used without restriction or modification and that no particularly new process is required for the use of the organopolysiloxane compounds of formula (I). In this respect, the present invention is entirely within the scope of the existing prior art in the manufacture of metal-clad laminates. What is new is the use of organopolysiloxane compounds of formula (I) for the production of metal-clad laminates, which has hitherto been unknown interests.

[0114] Impregnation is followed by a drying step to remove any solvent used. Conventional techniques are also used for the drying method. These include, in particular, thermally induced evaporation with or without vacuum. Appropriate adjustment of the reactivity and adhesion of the binder mixture used provides a composite that can be stored after this step under appropriate conditions, for example under cooling, and can then be further processed.

[0115] In the final step of the process, the binder formulation is polymerized, again by prior art methods, by heating an optional initiator for free radical polymerization to a temperature above its decomposition temperature, so that the binder formulation decomposes to generate free radicals and start the free radical polymerization of the binder formulation. In principle, radiation curing methods can also be used.

[0116] When using curing by hydrosilylation instead of free radical polymerization, temperatures need to be used in this step that can inactivate inhibitors used for the hydrosilylation catalyst used and cause the catalytic activity of the hydrosilylation catalyst.

[0117] This step is usually carried out at a high temperature, preferably 100 to 390°C, more preferably 100 to 250°C, particularly 130 to 200°C, and this temperature is operated for a time period of preferably 5 to 180 minutes, more preferably 5 to 150 minutes, particularly 10 to 120 minutes. In addition, it is common to apply an increased pressure in this step. The usual pressure is in the range of 1 to 10 MPa, more preferably 1 to 5 MPa, particularly 1 to 3 MPa.

[0118] The composite is laminated with a conductive metal layer in this second step by application of a layer of at least one selected metal on one or both sides of the composite consisting of the reinforcing layer and the binder formulation before curing. In other words, between the first step consisting of impregnation and drying and the second step comprising the chemical curing of the binder formulation, the composite from the first step is laminated with at least one type of conductive metal.

[0119] Useful conductive metals include at least one of the following: copper, stainless steel, gold, aluminum, silver, zinc, tin, lead, and transition metals. The thickness of the conductive layer and its shape, size or surface texture are in principle not limited. Preferably, the conductive metal layer has a thickness of 3 to 300 μm, more preferably 3 to 250 μm, in particular 3 to 200 μm. If two layers are used, the thickness of the two layers of at least one type of conductive metal can vary and need not be the same. It is particularly preferred that the conductive metal layer is copper, and that if two conductive layers of conductive metal are used, both layers are copper. Preferably, the conductive metal is used in the form of a foil of the metal of interest. The arithmetic mean roughness Ra of the metal foil used is preferably 2 μm or less, more preferably 1 μm or less, in particular 0.7 μm or less. The lower the surface roughness, the better the suitability of the respective foil for use in high frequency applications, which is a preferred object of the present invention. To improve adhesion between the composite of conductive metal layer and binder formulation and the reinforcing layer, various prior art methods may be used, such as the use of an adhesion mediating layer, electroplating or vapor deposition of the metal layer and the reinforcing layer on the composite of the binder formulation. The conductive metal layer may be placed directly on the composite of the binder formulation and the reinforcing layer or may be connected thereto by an adhesion mediating layer.

[0120] If no reinforcing layer is included, the layer of binder formulation comprising the organopolysiloxane compound of formula (I) is preferably produced by depositing the layer of binder formulation on a carrier, for example a separatory film or separator plate, suitable materials for said carrier are in principle from which the dried or cured binder formulation can be subsequently separated again, for example suitable materials are polytetrafluoroethylene, polyester, and the like.Separability and film-forming properties for each carrier material must be determined individually depending on the binder composition.What is said about the method remains equally applicable to this unreinforced variant.

[0121] Using the reinforced or unreinforced composite from the first step and the laminated composite from the second step, a multi-layer structure can be made by stacking multiple layers of the composite from the first step, for example alternating with the clad laminate from the second step, and then curing the previously uncured composite from the first step in essentially the same manner as for the manufacture of metal clad laminates. To make thicker layers, multiple layers of the reinforced or unreinforced composite from the first step can be stacked directly in succession.

[0122] As well as in the manufacture of metal clad laminates, the organopolysiloxane compounds of formula (I) may be used in corrosion protection formulations for the purpose of corrosion protection, particularly at high temperatures.

[0123] In addition, the organopolysiloxane compounds of formula (I) and formulations comprising them can also be used for corrosion protection of reinforcing steel in reinforced concrete. The corrosion inhibition effect in reinforced concrete is achieved both when the organopolysiloxane compounds of formula (I) and formulations comprising them are introduced into the concrete mixture before casting and curing them, and when the organopolysiloxane compounds of formula (I) or formulations comprising them are applied to the concrete surface after the concrete has hardened.

[0124] In addition to the purpose of corrosion protection for metals, the organopolysiloxane compounds of formula (I) may be used to manipulate further properties of a formulation comprising the organopolysiloxane compound of formula (I) or of a solid article or thin film obtained from a formulation comprising the organopolysiloxane compound of formula (I), for example: -Control of electrical conductivity and electrical resistance, - Controlling the flow properties of the formulation; - Controlling the gloss of wet or cured films or objects; -Improved weather resistance, -Improved chemical resistance, -Improved color stability, - Reduced tendency to choke, - an increase or decrease in the stick or sliding friction of solid articles or films obtained from formulations comprising organopolysiloxane compounds of formula (I), - stabilization or destabilization of foam in formulations comprising the formulation of the present invention, - improved adhesion to substrates of formulations comprising organopolysiloxane compounds of formula (I), - Control of filler behavior, pigment wetting behavior, and dispersion behavior, - control of the rheological properties of formulations comprising organopolysiloxane compounds of formula (I), control of mechanical properties, such as flexibility, scratch resistance, elasticity, extensibility, bendability, tear behavior, rebound behavior, hardness, density, tear propagation resistance, compression set, behavior at different temperatures, expansion rate, abrasion resistance, and further properties such as thermal conductivity, flammability, gas permeability, resistance to water vapor, heat, chemicals, weathering and radiation, sterilizability of obtainable solid articles or thin films comprising the organopolysiloxane compounds of formula (I) or formulations comprising them, -Control of electrical properties, such as dielectric loss factor, dielectric strength, dielectric constant, tracking resistance, arc resistance, surface resistance, specific dielectric strength, Control of the mechanical properties, such as flexibility, scratch resistance, elasticity, extensibility, bending, tear behavior, rebound behavior, behavior at different temperatures of solid articles or thin films obtainable from formulations comprising organopolysiloxane compounds of formula (I).

[0125] Examples of applications where the organopolysiloxane compounds of formula (I) may be used to manipulate the above properties are the production of coating compositions and impregnations and coatings and coated metals obtained therefrom on substrates such as metal, glass, wood, inorganic substrates, textiles, carpets, floor coverings or fibers, leather, plastics such as thin films, and synthetic and natural fibers for the production of other articles that can be produced from molded articles. With appropriate selection of formulation components, the organopolysiloxane compounds of formula (I) may be used in formulations as additives for the purposes of defoaming, flow promotion, hydrophobization, hydrophilization, filler and pigment dispersion, filler and pigment wetting, substrate wetting, promoting surface smoothness, reducing stick or sliding friction on the surface of the cured compound obtained from the additive-added formulation. The organopolysiloxane compounds of formula (I) may be incorporated into elastomeric compounds in liquid or cured solid form. Here, they may be used for the purposes of reinforcing or improving other performance properties, such as transparency, heat resistance, yellowing tendency or weather resistance control.

[0126] All of the above symbols in the above formulae are defined in each case independently of one another. In all of the formulae the silicon atom is tetravalent. EXAMPLES

[0127] The following examples will serve to further clarify the present invention: these examples should be understood as illustrative and not limiting.

[0128] All percentages are by weight. Unless otherwise specified, all operations are carried out at room temperature of 23° C. and standard pressure (1.013 bar).

[0129] Unless otherwise specified, all data for describing the product properties relate to room temperature of 23° C. and standard pressure (1.013 bar).

[0130] The equipment is a commercially available laboratory instrument commercially available from a number of equipment manufacturers.

[0131] Ph is the phenyl group =C6H5-.

[0132] Me is a methyl group, =CH3-. Thus, Me2 is two methyl groups.

[0133] The PPE is a polyphenylene ether.

[0134] HCl is hydrochloric acid.

[0135] In this document, materials are characterized by reporting data obtained by instrumental analysis. The underlying measurements are performed according to publicly accessible standards or are determined using specifically developed methods. To ensure clarity of the disclosed teachings, the methods used are specified hereinafter.

[0136] In all examples, reported parts and percentages are by weight unless otherwise specified.

[0137] viscosity: Unless otherwise specified, the viscosity is determined by a rotational viscometer in accordance with DIN EN ISO 3219. Unless otherwise specified, all viscosities relate to 25° C. and a standard pressure of 1013 mbar.

[0138] Refractive Index: Unless otherwise specified, the refractive index is determined in the visible light wavelength range, 589 nm, at 25° C. and a standard pressure of 1013 mbar according to standard DIN 51423.

[0139] Transmittance: The transmittance is determined by UV-VIS spectroscopy. A suitable device is, for example, the Analytik Jena Specord200.

[0140] The measurement parameters used were: range: 190–1100 nm, step width: 0.2 nm, integration time: 0.04 s, measurement mode: step mode.

[0141] A reference measurement (background) is first performed: a quartz plate mounted on a sample holder (quartz plate dimensions: height x width approx. 6 x 7 cm, thickness approx. 2.3 mm) is placed in the sample beam and measured against air.

[0142] After this, the sample is measured: the quartz plate mounted in the sample holder and containing the actual applied sample with a layer thickness of about 1 mm is placed in the sample beam and measured against air. An internal calculation against the background spectrum gives the transmittance spectrum of the sample.

[0143] Molecular composition: The molecular composition is 1 H nuclei and 29 It was determined by nuclear magnetic resonance spectroscopy (for terminology, see ASTM E386: High Resolution Nuclear Magnetic Resonance (NMR) Spectroscopy: Terminology and Symbols), which involves measurement of the Si nucleus.

[0144] 1 Explanation of H-NMR measurements Solvent: CDCl3, 99.8% D Sample concentration: Approximately 50mg / 1ml CDCl3 in a 5mm NMR tube Measured without added TMS, spectral reference to residual CHCl3 in CDCl3 at 7.24 ppm Spectrophotometer: Bruker Avance I 500 or Bruker Avance HD 500 Probe: 5mm BBO probe or SMART probe (Bruker) Measurement parameters: Pulse program = zg30 TD=64k NS=64 or 128 (depending on probe sensitivity) SW=20.6ppm AQ=3.17 seconds D1=5 seconds SFO1=500.13MHz O1=6.175ppm Processing parameters: SI=32k WDW=EM LB=0.3Hz

[0145] Depending on the spectrophotometer model used, individual adjustments to the measurement parameters may be necessary.

[0146] 29 Explanation of Si-NMR measurement Solvent: C6D6 99.8% D / CCl4 1:1 (vol / vol) containing 1 wt% Cr(acac)3 as a relaxation agent Sample concentration: Approximately 2g / 1.5ml solvent in a 10mm NMR tube Spectrophotometer: Bruker Avance300 Probe: 10mm 1 H / 13 C / 15 N / 29 Si glass-free QNP probe (Bruker) Measurement parameters: Pulse program = zgig60 TD=64k NS=1024 (depends on probe sensitivity) SW=200ppm AQ=2.75 seconds D1=4 seconds SFO1=300.13MHz O1=-50ppm Processing parameters: SI=64k WDW=EM LB=0.3Hz

[0147] Depending on the spectrophotometer model used, individual adjustments to the measurement parameters may be necessary.

[0148] Molecular weight distribution: The molecular weight distribution is determined as weight average Mw and number average Mn using the methods of gel permeation chromatography (GPC) and size exclusion chromatography (SEC) with polystyrene standards and a refractive index detector (RI detector). Unless otherwise specified, THF is used as the eluent and DIN 55672-1 is followed. Polydispersity is the ratio Mw / Mn.

[0149] Determination of dielectric properties: Df, Dk The dielectric properties are determined according to IPC TM 650 2.5.5.13 using a Keysight / Agilent E8361A network analyzer by the split cylinder resonator method at 10 GHz.

[0150] Synthesis example 1: Preparation of the organopolysiloxane compound of formula (I): Synthesis according to the procedure of DE 102005040323 A1, Example 1, leads to the results described herein: A mixture of 109 g of redistilled 1,2-bis(methyldichlorosilyl)ethane and 820 g of vinyldimethylchlorosilane is cooled to 10°C. With stirring and simultaneous cooling, a total of 1.7 l of 5% HCl solution is added over a period of about 80 minutes such that the temperature of the reaction mixture can be maintained between 10 and 20°C. The mixture is then stirred vigorously for 30 minutes, after which the phases are separated. The siloxane phase is washed four times with 1 l of water, neutralized with 0.5 l of 5% NaHCO3 solution, and washed again with 1 l of water. Volatile hydrolysis products (mainly divinyltetramethyldisiloxane) are removed under reduced pressure below 80°C. This results in a 7.2 mm 2 149.8 g of a clear liquid are obtained as residue with a viscosity of 0.001 g / s (25 °C) and an iodine value of 169.6 indicating exactly one C=C double bond per 149.8 g. The ratio of end groups to branching units is 2.57. The product contains about 90% of the hydrolyzed form of the 1,2-bis(methyldichlorosilyl)ethane used.

[0151] Synthesis example 2: Preparation of the silphenylene-bridged organopolysiloxane compound of formula (I).

[0152] Synthesis of silphenylene precursors: Xunjun Chen, Minghao Yi, Shufang Wu, Lewen Tan, Yixin Xu, Zhixing Guan, Jianfang Ge, and Guoqiang Yin: Synthesis of Silphenylene-Containing Siloxane Resins Exhibiting Strong Hydrophobicity and High Water Vapor Barriers, Coatings 2019,9,481;doi:10.3390 / coatings9080481 1,4-Bis(dimethoxyphenylsilyl)benzene following literature procedures at www.mdpi.com / journal / coatings. 1,4-bis(dimethoxyphenylsilyl)benzene is obtained by reacting trimethoxyphenylsilane with a Grignard reagent obtained from 1,4-dibromobenzene according to the reference "2.2. Synthesis of the 1,4-bis(dimethoxyphenylsilyl)benzene (BDMPD)". The structure is 1 Confirmation was achieved by 1 H-NMR spectroscopy and comparison with literature references.

[0153] A mixture of 845.2 g (=4 mol) of phenyltrichlorosilane, 546.7 g (1.3 mol) of 1,4-bis(dimethoxyphenylsilyl)benzene, 198.7 g (0.8 mol) of 3-trimethoxysilylpropyl methacrylate and 820 g of xylene is metered into an initial charge of 2400 g of demineralized water over a period of 4 hours. The initial charge is carried out at the start of the metering at room temperature of 23° C. The temperature rises as a result of the exothermic release of heat during the reaction. The metering is controlled so that the internal temperature of the reactor never rises above 50° C. If necessary, the metering rate is reduced.

[0154] At the end of the metered addition, the mixture is stirred for 15 minutes. The stirrer is then stopped. The organic and aqueous phases are separated. The lower aqueous clear and colorless phase, consisting essentially of concentrated aqueous hydrochloric acid, is drained off.

[0155] To the organic phase remaining in the reaction vessel, 1 l of demineralized water is added and the vessel contents are mixed by stirring. After 30 minutes, the stirrer is stopped and the phases are allowed to separate again. The aqueous phase sinks as the lower phase and is allowed to run off. If the aqueous phase sinks as the lower phase, the mixture is washed again for 30 minutes with 10% aqueous sodium chloride solution instead of demineralized water or with an addition of 100 g of sodium chloride, after which the phase separation is carried out again. This process is repeated until the residual HCl content in the organic phase is less than 20 ppm. The residual HCl content is determined by acid-base titration according to the prior art. Usually, two washes with demineralized water or 10% aqueous NaCl solution are sufficient. Water is then removed by azeotropy at 110° C. with xylene as the water entrainer until no more water is obtained.

[0156] The product obtained at this stage of the synthesis contains about 3% by weight of silanol groups, which interfere with the target application due to their polarity. To reduce the silanol content, the following procedure is used:

[0157] 200 g of water are metered into the xylene reaction mixture remaining after the distillation. 265.1 g (2.2 mol) of vinyldimethylchlorosilane are then added slowly, adjusting the metering rate so that the reaction temperature (internal temperature of the reactor) remains below the limit of 50° C. At the end of the metering, the mixture is stirred for a further 60 minutes without heating or cooling so that the reaction of the silanol groups with the vinyldimethylchlorosilane or tetramethyldivinyldisiloxane formed therefrom proceeds to completion.

[0158] The aqueous phase is removed as above, and the mixture is then washed three times with 1 liter of water as above. If necessary, phase separation can be accelerated by stopping the stirrer and heating to a heating jacket temperature of 60° C. After washing, the HCl content in the xylene solution is less than 20 ppm.

[0159] The amount of xylene is reduced by distillation under reduced pressure (20 mbar) at 110° C. until a solution of 80% resin in 20% xylene is obtained.

[0160] The methoxy group is no longer present in the resulting product. 1 1 H NMR, indicating that the methacrylate-functional trimethoxysilane was completely incorporated by condensation; the resulting methanol was removed during workup. Further treatment reduced the proportion of silanol groups to about 0.9 wt.% ( 1 The temperature is reduced to 1 H (determined by 1 H NMR).

[0161] The following molecular weights were determined by SEC (eluent toluene): Mw=7347 g / mol, Mn=2903 g / mol, polydispersity PD=2.53.

[0162] 29 By Si NMR, the molar composition of the silicon-containing portion of the formula is: Me2Si(Vi)O 1 / 2 :11.54% H2C=C(CH3)C(=O)-O-(CH2)3-SiO 3 / 2 :11.98% O 2 / 2 (Ph)Si-C6H4-Si(Ph)O 2 / 2 :19.23% PhSiO 3 / 2 :57.25% It is.

[0163] The silanol group is PhSiO 3 / 2 It is connected to the unit.

[0164] Synthesis example 3: Preparation of organopolysiloxane compounds of formula (I) having phenylene bridges: The synthesis is repeated according to Synthesis Example 2, but using the following amounts of starting materials instead of those in Synthesis Example 2: Phenyltrichlorosilane: 281.7g (=1.3 mol) 1,4-Bis(dimethoxyphenylsilyl)benzene: 1202.7 g (2.9 mol).

[0165] The rest of the procedure is the same as in Synthesis Example 3. The following results are obtained: No methoxy groups are detectable by NMR. The residual silanol content is 0.8% by weight.

[0166] SEC: Mw = 8347 g / mol, Mn = 3953 g / mol, polydispersity PD = 2.11.

[0167] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :10.93% H2C=C(CH3)C(=O)-O-(CH2)3-SiO 3 / 2 :10.89% O 2 / 2 (Ph)Si-C6H4-Si(Ph)O 2 / 2 :49.96% PhSiO 3 / 2 :28.22% It is.

[0168] Synthesis example 4: Preparation of organopolysiloxane compounds of formula (I) having alkylene bridges: The synthesis according to Synthesis Example 2 is repeated, but using the following starting materials in place of those in Synthesis Example 2 in the following amounts: Phenyltrichlorosilane: 422.6g (=2 moles) 1,2-Bis(dichloromethylsilyl)ethane: 341.35g (1.35mol) Vinyldimethylchlorosilane: 403.7 g (3.35 mol) Do not use 1,4-bis(dimethoxyphenylsilyl)benzene.

[0169] In this synthesis, 271.2 g (2.25 mol) of vinyldimethylchlorosilane are added directly to the mixture of chlorosilanes metered into the initial charge of water in the first step. The remaining 132.6 g (1.1 mol) are used for the reduction of silanol groups as in Synthesis Example 3.

[0170] The rest of the procedure is the same as in Synthesis Example 3. The following results are obtained: No methoxy groups are detectable by NMR. The residual silanol content is 0.9% by weight. SEC: Mw=6974 g / mol, Mn=2812 g / mol, polydispersity PD=2.48.

[0171] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :50.39% O 2 / 2 (Me)Si-C2H4-Si(Me)O 2 / 2 :19.56% PhSiO 3 / 2 :30.05% It is.

[0172] Synthesis example 5: Preparation of organopolysiloxane compounds of formula (I) having alkylene and phenylene bridges: The synthesis is repeated according to Synthesis Example 2, but using the following amounts of starting materials instead of those in Synthesis Example 2: Phenyltrichlorosilane: 422.6g (=2 moles) 1,2-Bis(dichloromethylsilyl)ethane: 512.0 g (2 moles) 1,4-Bis(dimethoxyphenylsilyl)benzene: 986.2 g (2.4 mol) Vinyldimethylchlorosilane: 403.7 g (3.35 moles).

[0173] In this synthesis, 271.2 g (2.25 mol) of vinyldimethylchlorosilane are added directly to the mixture of chlorosilanes metered into the initial charge of water in the first step. The remaining 132.6 g (1.1 mol) are used for the reduction of silanol groups as in Synthesis Example 3.

[0174] The rest of the procedure is the same as in Synthesis Example 3. The following results are obtained: No methoxy groups are detectable by NMR. The residual silanol content is 0.9% by weight. SEC: Mw=4974 g / mol, Mn=1966 g / mol, polydispersity PD=2.53.

[0175] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :34.49% O 2 / 2 (Me)Si-C2H4-Si(Me)O 2 / 2 :20.31% O 2 / 2 (Ph)Si-C6H4-Si(Ph)O 2 / 2 :24.64% PhSiO 3 / 2 :20.56% It is.

[0176] Synthesis Example 6: Preparation of organopolysiloxane compounds of formula (I) having alkylene and phenylene bridges: The synthesis is repeated according to Synthesis Example 6, but using the following amounts of starting materials instead of those in Synthesis Example 6: 1,2-Bis(trimethoxysilyl)ethane: 540.0 g (2 moles) In this example, 1,2-bis(dichloromethylsilyl)ethane is not used.

[0177] The rest of the procedure is the same as in Synthesis Example 6. The following results are obtained: No methoxy groups are detectable by NMR. The residual silanol content is 0.8% by weight. SEC: Mw=5768 g / mol, Mn=2074 g / mol, polydispersity PD=2.78.

[0178] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :32.78% O 3 / 2 Si-C2H4-SiO 3 / 2 :21.01% O 2 / 2 (Ph)Si-C6H4-Si(Ph)O 2 / 2 :23.48% PhSiO 3 / 2 :22.73% It is.

[0179] Synthesis Example 7: Preparation of organopolysiloxane compounds of formula (I) having alkylene bridges: The synthesis according to Synthesis Example 6 is repeated, but using the following starting materials in place of those in Synthesis Example 6 in the following amounts: 1,2-Bis(chlorodimethylsilyl)ethane: 580.6 g (2.7 mol) Do not use 1,2-bis(dichloromethylsilyl)ethane. Do not use 3-trimethoxysilylpropyl methacrylate.

[0180] The rest of the procedure is the same as in Synthesis Example 3. The following results are obtained: No methoxy groups are detectable by NMR. The residual silanol content is 0.8% by weight. SEC: Mw=5637 g / mol, Mn=1964 g / mol, polydispersity PD=2.87.

[0181] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :11.96% O 1 / 2 (Me2)Si-C2H4-Si(Me2)O 1 / 2 :19.56% PhSiO3 / 2 :68.48% It is.

[0182] Comparative Example 1: Synthesis of organopolysiloxanes not containing crosslinked SiC-bonded units according to the present invention The synthesis according to Synthesis Examples 2, 3, and 4 is repeated, but, deviating from Synthesis Examples 2 to 4, no raw material having a bridging unit is used, which means that neither 1,4-bis(dimethoxyphenylsilyl)benzene nor 1,2-bis(dichloromethylsilyl)ethane is used. The amounts shown for these ingredients are substituted as follows:

[0183] In synthesis example 2, 1,4-bis(dimethoxyphenylsilyl)benzene is not used or otherwise the synthesis is carried out unchanged as shown. Result: Product specification V1.2

[0184] No residual methoxy content was detectable by 1H-NMR, and the silanol content is 1.1 wt%.

[0185] The following molecular weights were determined by SEC (eluent toluene): Mw=3657 g / mol, Mn=1759 g / mol, polydispersity PD=2.07.

[0186] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :14.96% H2C=C(CH3)C(=O)-O-(CH2)3-SiO 3 / 2 :15.81% PhSiO 3 / 2 :69.23% It is.

[0187] In Synthesis Example 3, a specific amount of 1,4-bis(dimethoxyphenylsilyl)benzene is replaced by phenyltrichlorosilane on a molar equivalent basis. All other information remains unchanged. Result: Product specification V1.3

[0188] No methoxy groups are detected by NMR. The residual silanol content is 1.0% by weight. SEC: Mw=3477 g / mol, Mn=1385 g / mol, polydispersity PD=2.51.

[0189] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :11.03% H2C=C(CH3)C(=O)-O-(CH2)3-SiO 3 / 2 :11.36% PhSiO 3 / 2 :77.61% It is.

[0190] In Synthesis Example 4, a specific amount of 1,4-bis(dimethoxyphenylsilyl)benzene is replaced by phenyltrichlorosilane on a molar equivalent basis. All other information remains unchanged. Result: Product specification V1.4

[0191] No methoxy groups are detectable by NMR. The residual silanol content is 0.9% by weight. SEC: Mw=1576 g / mol, Mn=885 g / mol, polydispersity PD=1.78.

[0192] 29 By Si NMR, the molar composition of the silicon-containing portion of the formulation was: Me2Si(Vi)O 1 / 2 :51.35% PhSiO 3 / 2 :48.65% It is.

[0193] Use Example 1: Use of the organopolysiloxanes according to synthesis examples 1 to 7 for the production of metal-clad laminates and comparison with comparative examples V1.2, V1.3 and V1.4 The organopolysiloxanes prepared according to Synthesis Examples 1-7 and according to the Comparative Example were used as binders to produce copper clad laminates with glass fiber reinforced composite layers. The following input materials were used:

[0194] Copper foil: 35 μm thick copper foil (285±10 g / m2) from Jiangtong-Yates Copper Foil Co Ltd, with a ten-point average roughness Rz of ≦8 μm and an arithmetic mean roughness Ra of ≦0.4 μm, and a purity of ≧99.8%. 2 ).

[0195] Glass fiber: E-glass fiber type 1080E manufactured by Changzhou Xingao Insulation Materials Co. Ltd. Thickness 0.055±0.012mm, 47.5±2.5g / m 2 .

[0196] In this example, the organopolysiloxane from synthesis example 1 was used solvent-free, all others in the form of a solution in xylene. For the organopolysiloxanes from synthesis examples 4, 5, 6, and 7 and comparative example V1.4, in each case the solution contained 90% organopolysiloxane and 10% xylene. For the organopolysiloxanes from synthesis examples 2 and 3 and comparative examples V1.2 and V1.3, a formulation of 80% organopolysiloxane and 20% xylene was used.

[0197] To initiate curing, in each case the organopolysiloxane was mixed with 1% by weight of dicumyl peroxide, which was uniformly dispersed in the resin matrix by stirring.

[0198] The laminates were produced by bubble-free impregnation, layer by layer, of the respective organopolysiloxane, optionally in the form of a xylene solution, using a bleeder roller of a 30 x 30 cm glass fiber layer. For this, the glass fiber layer was placed on a dimensionally stable stainless steel flat surface, on which a layer of copper foil was placed, and then a first layer of glass fiber was placed on top of it. A total of three layers of glass fiber fabric were impregnated each time in succession. To remove any solvent present, the impregnated fabric was dried to constant weight in a vacuum oven at 60 ° C and 10 mbar. A second layer of copper foil was then superimposed on the impregnated glass fiber layer, and another dimensionally stable stainless steel plate was placed on top of it. The laminate was heated in a heated press at 2 MPa pressure at 200 ° C and 30 mbar vacuum for 120 minutes. A copper-clad laminate with a total thickness of 260 ± 20 μm was obtained.

[0199] The dielectric properties were determined according to IPC TM 650 2.5.5.13 using a Keysight / Agilent E8361A network analyzer by the split cylinder resonator method at 10 GHz. The values ​​reported in Table 1 were obtained:

[0200] [Table 1]

[0201] D of the copper clad laminate obtained using the organopolysiloxane compound of formula (I) k Value and D f The values ​​are the D values ​​obtained with the organopolysiloxanes from the comparative examples. k Value and D f Since the objective for high frequency applications is the lowest possible dielectric loss factor and dielectric constant, the advantage of the present invention is evident.

[0202] Use Example 2: Use of the organopolysiloxanes according to synthesis examples 1 to 7 and the organopolysiloxane according to comparative example 1 for the production of metal-clad laminates with fillers Deviating from Example 1, 49.5% of Type Q 033 precipitated silica (manufacturer Suzhou Ginet New Materials Technology Co Ltd, spherical silicon dioxide particles, D 99 ≦3 μm, SiO2≧99%) was homogeneously incorporated into the resin solution using resin and commercial solubilizer. For resin formulations using xylene in Use Example 1, 30% and 40% xylene were used instead of 10% and 20% xylene, respectively.

[0203] Instead of directly stacking the laminates without a prepreg intermediate, the glass fiber layers were then produced by impregnating them with the resin formulation, in each case as individual layers on a polytetrafluoroethylene film, and then drying them to constant weight in a vacuum dryer. Thus, in each case, three layers of the impregnated glass fiber fabric thus produced were then stacked one on top of the other, on top of the copper foil and the stack completed with the copper foil layer. In a manner similar to that of use example 1, this multi-layer assembly was pressed between two dimensionally stable stainless steel plates in a vacuum press under the conditions specified in example 1.

[0204] The resulting laminate had a thickness of 290±20 μm. The resulting laminate exhibited the dielectric property measurements reported in Table 2.

[0205] [Table 2]

[0206] The increase in Dk and Df is due to further polar effects at the interface between the precipitated silica and the organopolysiloxane, but the inventive manufacture of metal-clad laminates using organopolysiloxane compounds of formula (I) still works well and is advantageous compared to non-inventive organopolysiloxanes, which is still evident.

[0207] Use Case 3: Selected synthesis using very viscous solid materials via prepreg Deviating from Use Example 2, no filler was used this time. Under these conditions, it is possible to produce prepregs using only organopolysiloxanes that dry to a sufficiently tack-free state. Therefore, for this example, only the organopolysiloxanes from Synthesis Examples 2 to 7 and the organopolysiloxanes V1.2 and V1.3 from Comparative Example 1 were used. These were used diluted with 10% and 20% xylene, as shown in Use Example 1. The organopolysiloxanes from Synthesis Example 1 are nevertheless the invention, since the possibility of producing tack-free prepregs is also satisfied here, if this is done by suitable means, such as by filling with suitable fillers or mixing with other organopolysiloxanes or suitable organic polymers. Since these are means for making formulations according to the prior art for the production of binder formulations for metal-clad laminates, prepregs produced from pure organopolysiloxane compounds of formula (I) without further compounding means are not inconsistent with the means of the invention.

[0208] Otherwise the procedure is the same as that described in Use Case 2.

[0209] The resulting laminate had a thickness of 270±20 μm. The resulting laminate exhibited the dielectric property measurements reported in Table 3.

[0210] [Table 3]

[0211] D of the copper clad laminate obtained using the organopolysiloxane of the present invention k Value and D f The values ​​are the D values ​​obtained with the organopolysiloxanes from the comparative examples. k Value and D f Since the objective for high frequency applications is the lowest possible dielectric loss factor and dielectric constant, the advantage of the present invention is evident.

[0212] Use Example 4: Use of the organopolysiloxanes according to Synthesis Examples 1 to 7 and Comparative Example 1 in mixtures with organic polymers for the production of metal-clad laminates. The procedure was essentially the same as that described in Use Example 2. In deviation from Use Example 2, no filler was used.

[0213] Instead, the organic polymer was mixed with the organopolysiloxane. The final solvent-free mixture always contained 30% by weight of the organopolysiloxane and 70% by weight of the organic polymer. The organic polymers used were triallyl isocyanurate (NORYL SA9000), α,ω-methacrylate terminated polyphenylene ether (SABIC, Mn=2500 g / mol, Tg=160° C.), and B3000 (Nippon Soda Co., Ltd., liquid polybutadiene containing more than 85% 1,2-vinyl structures in the polymer chain, Mn=3200, viscosity at 45° C.=210 poise).

[0214] The polymers were always used in the same proportions. They were dissolved / dispersed in xylene with 30 parts by weight of SA9000, 25 parts by weight of B3000, and 15 parts by weight of triallyl isocyanurate dispersed in 100 parts by weight of xylene.

[0215] The formulation thus obtained was mixed with a solution of organopolysiloxane prepared according to Use Example 2 such that a specific mixture ratio of 30% organopolysiloxane and 70% organic component was present in the resulting solution. These solutions were then used to manufacture the prepregs described in Use Example 2.

[0216] The resulting laminate had a thickness of 290±20 μm. The resulting laminate exhibited the dielectric property measurements reported in Table 4.

[0217] [Table 4]

[0218] D of the copper clad laminate obtained using the organopolysiloxane of the present invention k Value and D f The values ​​are the D values ​​obtained with the organopolysiloxanes from the comparative examples.k Value and D f Since the objective for high frequency applications is the lowest possible dielectric loss factor and dielectric constant, the advantage of the present invention is evident.

Claims

1. Formula (I): [(]))) a (3)) a ())) b ] c () 1 three) 3/2 ) d () 2 2 three) 2/2 ) e () 3 3 three) 1/2 ) f ( ) - 4/2 ) g () A metal-clad laminate comprising a crosslinkable organic polysiloxane compound represented by the formula (I): R, which may be the same or different, is a hydrogen group or a monovalent Si-C bonded organic hydrocarbon group having 1 to 18 carbon atoms and optionally substituted with heteroatoms; Y is a divalent to dodecavalent organic group having 1 to 24 carbon atoms and optionally substituted with heteroatoms, said group Y being always bonded by a Si-C bond to the silicon atoms which are interconnected by said group Y; R 1 are each independently a hydrogen group or a SiC-bonded unsaturated C1-C18 hydrocarbon group which may be substituted by a heteroatom and which may be bonded to a silicon atom by an oxygen atom, and the group R 1 may assume these meanings independently of one another, so that in the organopolysiloxanes according to formula (I) several radicals R 1 may be a group different from the groups defined above, group R 2 and R 3 are each independently a hydrogen group, or a SiC-bonded C1-C18 hydrocarbon group which may be substituted by a heteroatom and may be unsaturated, or a C1-C12 hydrocarbon group which may contain a heteroatom and may be bonded by an oxygen atom, and the group R 2 and the group R 3 may assume each of these meanings independently of one another, so that several groups R 2 or a plurality of groups R 3 may be a group different from the groups defined above, All SiC-bonded groups Y, R, R 1 , R 2 , and R 3 At least 0.1 mole percent, based on 100 mole percent, must be aliphatically unsaturated groups; a is 0, 1 or 2, and the subscript a on either side of the group Y may assume each of these meanings independently of one another, so that different a may, independently of one another, be different values ​​within the specified range of values, b is a number having a value from 1 to 11; c is a value between 0.1 and 0.99; d is a value between 0 and 0.8; e is a value between 0 and 0.5; f is a value between 0.01 and 0.6; g is a value between 0 and 0.2; c+d+e+f+g=1; Metal clad laminate.

2. The hydrocarbon groups R and R 1 , R 2 , and R 3 2. The metal clad laminate of claim 1, wherein is selected from methyl, phenyl, vinyl, acryloyloxy and methacryloyloxy groups, and acrylic or methacrylic acid esters of unbranched or branched alcohols having 1 to 15 carbon atoms.

3. 3. The metal clad laminate of claim 1 or 2, wherein Y is divalent, trivalent or tetravalent.

4. The metal clad laminate of any one of claims 1 to 3, wherein the metal clad laminate comprises a formulation comprising the organopolysiloxane compound of formula (I) and further components.

5. 5. The metal clad laminate according to claim 4, wherein the further constituents are selected from hydrosilylation catalysts, initiators for free radical polymerization, organic binders, solvents, formulation ingredients, adhesion promoters, curing initiators, catalysts, stabilizers, fillers, inhibitors, flame retardants, crosslinking coagents, antioxidants, stabilizers against degradation by weathering, lubricants, plasticizers, colorants, phosphorescent agents, other agents for marking and traceability purposes, and antistatic agents.

6. The metal clad laminate according to any one of claims 1 to 5, wherein the metal is copper.

Citation Information

Patent Citations

  • Crosslinkable silicone coating composition

    JP2009144161A

  • Organopolysiloxane and method for producing the same

    JP2009506003A

  • Hot-melt curable silicone composition for compression molding or lamination

    JP2016504461A

  • Organo-silicone resin aluminum-based copper-clad laminate and its preparation method

    JP2018523592A

  • Curable hot-melt silicone composition, cured material thereof, and laminate containing the composition or cured material

    JP2021107550A